6p+p+2-3=8p-8
7p-1=8p-8
1=1p-8
7=1p
p=7
Answer:
32,000
Step-by-step explanation:
Answer:
x = 11
Step-by-step explanation:
Given the expression;
5x+2y=67 ...1
x=3y−7 ....2
Substitute 2 into 1
5(3y-7)+2y = 67
15y - 35 + 2y = 67
17y = 67+35
17y = 102
y = 102/17
y =6
Recall that x = 3y - 7
x = 3(6) - 7
x = 18 - 7
x = 11
Hence the value of x is 11
Answer:
square, anddddddddddddddddd deskkkkkk I thinkjkkkkk
Answer:
(-8/7 ; 5/7)
Step-by-step explanation:
5t + 1/2s = 3 - - - (1)
3t - 6s = 9 - - - - - (2)
Multiply (1) by 12 and (2) by 1
Add the result to eliminate s
60t + 6s = 36
3t - 6s = 9
____________
63t = 45
t = 45 / 63
t = 5/7
Put t = 5/7 in either (1) or (2) to obtain the value of s
3(5/7) - 6s = 9
15/7 - 6s = 9
-6s = 9 - 15/7
-6s = (63 - 15)/7
-6s = 48/7
s = 48/7 * - 1/6
s = - 8/7